2019
DOI: 10.1097/md.0000000000013952
|View full text |Cite
|
Sign up to set email alerts
|

The association of depression following percutanous coronary intervention with adverse cardiovascular events

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(32 reference statements)
0
9
0
3
Order By: Relevance
“…Clinically, reports in various regions on the number of patients readmitted to the ICU after cardiac surgery vary, and have reached as high as 19% (18)(19)(20). In a meta-analysis by Hughes et al (21) of 4,417 patients with surgically corrected coronary heart disease, the proportion of patients readmitted to the ICU was 10.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, reports in various regions on the number of patients readmitted to the ICU after cardiac surgery vary, and have reached as high as 19% (18)(19)(20). In a meta-analysis by Hughes et al (21) of 4,417 patients with surgically corrected coronary heart disease, the proportion of patients readmitted to the ICU was 10.2%.…”
Section: Discussionmentioning
confidence: 99%
“…In [ 14 ], the study also found that the negative and rejection attitude of the public towards mental illness has changed little or even worsened over the years. Literature [ 15 ] holds that it is necessary to encourage the patient's spirit of tenacious struggle against the disease, mobilize the patient's subjective initiative to fight against the disease, and work with doctors to obtain the patient's cooperation and improve the curative effect. According to [ 16 ], identifying the harbinger of disease recurrence can encourage patients to see a doctor sooner rather than later, thereby controlling symptoms, significantly improving discharged mental patients' compliance, and effectively lowering the recurrence rate.…”
Section: Related Workmentioning
confidence: 99%
“…Não deve também ser ignorado o fato de que a experiência da doença crônica pode agir negativamente sob a influência psicológica e prática de exercícios, uma vez que o medo de acentuar a doença "do coração" pode ser maior que o encorajamento de atingir os proventos advindos do exercício (FORECHI et al, 2018). Nesse contexto, os estados emocionais negativos, como a ansiedade e depressão, estão associados ao desenvolvimento e progressão das DCVs (VOGELZANGS et al, 2010;NAJAFIPOUR et al, 2016;CHAUVET-GELINIER;BONIN, 2017) e muitos estudos mostram a influência desses sintomas em pessoas que sofreram algum evento cardíaco (GU et al, 2016;NAJAFIPOUR et al, 2016;FENG et al, 2017;PRUGGER et al, 2017;LIU et al, 2019).…”
Section: Discussionunclassified
“…Essa autora não encontrou evidências de diminuição de casos de depressão entre os grupos controle e intervenção. Liu et al (2019), em protocolo para revisão sistemática e metanálise, consideram que, embora nem todos os mecanismos que associem a depressão ao procedimento de ICP sejam conhecidos, sabe-se que a depressão se agrava pela relação com o estilo de vida pouco saudável, baixo comprometimento com os medicamentos, função endotelial comprometida, disfunção neuroendócrina e fatores de risco em comum (tabagismo, obesidade, dislipidemia e diabetes). Entretanto, a RCV e o aconselhamento pré-alta são capazes de melhorar o prognostico da doença (LIU et al, 2019), por ser também considerada como o melhor momento para gerenciar emoções negativas e distúrbios psicológicos em cardiopatas (CHAUVET-GELINIER; BONIN, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation